A-80426 suppresses CFA-induced inflammatory pain by suppressing TRPV1 activity via NFκB and PI3K pathways in mice (Clinics, 2023)
Objectives: Pain is associated with many circumstances, including inflammatory reactions, which arise from modification of the features of signaling pathways. α2-adrenergic receptor antagonists are widely utilized in narcosis. Here, the authors focused on the narcotic effect of A-80426 (A8) on Complete Freund's Adjuvant (CFA) injections-triggered chronic inflammation pain in WT and TRPV1-/- mice and explored whether its antinociceptive impact was modulated via Transient Receptor Potential Vanilloid 1 (TRPV1).Method: CFA with or without A8 was co-administered to the mice, which were categorized randomly into four groups: CFA, A8, control, and vehicle. Pain behaviors underwent evaluation through mechanical withdrawal threshold, abdominal withdrawal reflex, and thermal withdrawal latency of WT animals.Results: Quantitative polymerase chain reaction revealed that inflammation-promoting cytokines (IL-1β, IL-6, and TNF-α) were upregulated in Dorsal Root Ganglion (DRG) and Spinal Cord Dorsal Horn (SCDH) tissues of WT animals. A8 administration reduced the pain behaviors and production of pro-inflammatory cytokines; however, this effect was significantly reduced in TRPV1-/- mice. Further analysis showed that CFA treatment reduced the TRPV1 expression in WT mice and A8 administration increased its expression and activity. The co-administration of SB-705498, a TRPV1 blocker, did not influence the pain behaviors and inflammation cytokines in CFA WT mice; however, SB-705498 the effect of A8 in WT mice. In addition, the TRPV1 block decreased the NFκB and PI3K activation in the Dorsal Root Ganglia (DRG) and Spinal Cord Dorsal Horn (SCDH) tissues of WT mice.Conclusions: Together, A8 exerted a narcotic impact on CFA-supplemented mice via the TRPV1-modulated NFκB and PI3K pathway.